Role of the Policy Environment in Shaping the Work of Professional Learning Partnerships - Kirsten Lee Hill; Laura Desimone; Latrice Marianno; Camila Polanco; Teresa Bendel (AERA Open)
Building on previous work studying research–practice partnerships, we use the framework of policy attributes to explore success and resilience in organizations tasked with quickly adapting to serving teachers and students in school environments vastly changed by the COVID-19 pandemic. This study leveraged survey and interview data from 12 partnerships located in large urban school districts in the United States to understand how the policy environment of partnerships facilitates success. Although previous literature emphasized the importance of all policy attributes in successful partnership work, we found that only high specificity (having a shared clear understanding of roles, responsibilities, and objectives) and the presence of robust authority (strong buy-in and sufficient resources) are most critical for organizational success.